2014
DOI: 10.4103/0377-4929.134676
|View full text |Cite
|
Sign up to set email alerts
|

Establishing biological reference intervals for novel platelet parameters (immature platelet fraction, high immature platelet fraction, platelet distribution width, platelet large cell ratio, platelet-X, plateletcrit, and platelet distribution width) and their correlations among each other

Abstract: These novel platelet parameters offer newer avenues in research and clinical use. Establishing biological reference interval for different platelet parameters would help determine true high and low values and help guide treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 0 publications
3
33
1
3
Order By: Relevance
“…In contrast with previous studies, we reported an inverse association between p-LCR and acute presentation [37], while we confirmed the well-established relationship between platelets count and size [38], thus suggesting that p-LCR could represent a Breactive^condition of increased consumption of circulating platelets, with the release in the bloodstream of larger, immature fractions, of platelets. In fact, higher levels of thrombopoietin, a key hormone in thrombopoietic signalling, have been related to platelet size in CAD patients [39,40].…”
Section: Discussionsupporting
confidence: 57%
“…In contrast with previous studies, we reported an inverse association between p-LCR and acute presentation [37], while we confirmed the well-established relationship between platelets count and size [38], thus suggesting that p-LCR could represent a Breactive^condition of increased consumption of circulating platelets, with the release in the bloodstream of larger, immature fractions, of platelets. In fact, higher levels of thrombopoietin, a key hormone in thrombopoietic signalling, have been related to platelet size in CAD patients [39,40].…”
Section: Discussionsupporting
confidence: 57%
“…[4,5]. As different autoanalyzer can have different values, making it difficult to compare between studies, necessitating each study define its mean [27][28][29][30]. In Dengue illness an MPV of less than nine has been suggested to have a diagnostic potential with a high reported sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…5 The normal range for MPV in Indian population is from 8.6-15.5 fL. 6 PDW is a marker of volume variability in platelets size and is elevated in the presence of platelet anisocytosis. 7 The PDW reported varies with reference intervals ranging from 8.3 to 56.6%.…”
Section: Platelet Indicesmentioning
confidence: 99%